"That's the Experience": Passion, Work Precarity, and Life Transitions Among London Jazz Musicians. (August 2015) - Umney, Charles; Kretsos, Lefteris
This article looks at early-career jazz musicians working in London. It links sociological literature on precarity and the life course with a more specific focus on the process of establishing a career in music. It shows how participants sought to embrace and sometimes even manufacture greater precarity in their working lives, and how they contextualized it as part of the life course. Their ability to manage precarity in this way, however, was greatly affected by structural factors, specifically socioeconomic background. Particular elements that are especially pronounced in creative work, such as the prominence of project-based employment and the importance of passion for the job, are important factors leading to the management and indefinite extension of these transitional periods.